2021
DOI: 10.1186/s13048-021-00886-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular response to PARP1 inhibition in ovarian cancer cells as determined by mass spectrometry based proteomics

Abstract: Background Poly (ADP)-ribose polymerase (PARP) inhibitors have entered routine clinical practice for the treatment of high-grade serous ovarian cancer (HGSOC), yet the molecular mechanisms underlying treatment response to PARP1 inhibition (PARP1i) are not fully understood. Methods Here, we used unbiased mass spectrometry based proteomics with data-driven protein network analysis to systematically characterize how HGSOC cells respond to PARP1i treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…One of the promising therapeutic perspectives is the use of DNA-dependent nuclear enzymes, such as poly(adenosine diphosphate-ribose) polymerase (PARP) [ 160 ]. PARP are the main enzymes activated in the response to DNA damage [ 161 ]. Currently, PARP inhibitors (PARPi) are used in first-line, second-line, or maintenance therapy after platinum-based chemotherapy [ 162 , 163 ].…”
Section: Therapymentioning
confidence: 99%
“…One of the promising therapeutic perspectives is the use of DNA-dependent nuclear enzymes, such as poly(adenosine diphosphate-ribose) polymerase (PARP) [ 160 ]. PARP are the main enzymes activated in the response to DNA damage [ 161 ]. Currently, PARP inhibitors (PARPi) are used in first-line, second-line, or maintenance therapy after platinum-based chemotherapy [ 162 , 163 ].…”
Section: Therapymentioning
confidence: 99%
“…We previously reported that peripheral TCR analysis and early ctDNA dynamics could predict clinical response to ICIs [32]. Franz et al reported that the clinical utility of proteomic analysis may clarify the responders to PAPRi [33]. Given the additional effect of PAPRi for modulating the tumor microenvironment and cancer-specific T cells, our combined novel analysis could identify the subgroup that shows a good response to this combination therapy.…”
Section: Discussionmentioning
confidence: 95%
“…In a phase I clinical trial, TVB-2640 effectively reduced fatty acid production in patients with non-small cell lung cancer. In subsequent clinical trials for breast and ovarian cancer, TVB-2640 exhibited favorable clinical activity and safety, with no gastrointestinal or serum toxicity observed ( 101 , 102 ). Adverse events were mainly mild and included skin and eye effects, which were manageable with appropriate measures.…”
Section: Treatmentmentioning
confidence: 99%